Kriptografi Dan Kompresi Pesan Singkat Pada Android - Pizaini Pizaini; Febi Yanto (UIN Sultan Syarif Kasim Riau, 2012)
Communication via Short Message Service (SMS) messaging is a technology that still has some problems that limited message size and message content security. Message size is greater than 140 bytes are sent over the SMS and the message can be read by others if they have access to the SMS Center. Implementation of cryptographic and compression on the SMS message can increase security and improve the efficiency of the delivery of the message. Algorithm Advanced Encryption Standard (AES) is one of the reliable cryptographic methods to secure data and combined with Huffman compression that uses statistical principles to produce data that are smaller. The combination of encryption and compression can result in four modes, namely messaging Only Compress, Compress and Encrypt, Encrypt and Compress and Encrypt Only. Only Compress delivery mode can reduce the size of the message with a compression ratio of 72.87%. Only while the Encrypt transmission mode can improve the security of a message, but it produces a larger message of the original message. If the combined compression and encryption menghasilakan compression ratio of 75.94%.Keywords: AES, Encryption, Huffman, Compression, SMS